UPAYA MENINGKATKAN NASIONALISME REMAJA KOTA SURAKARTA DALAM MENGHADAPI KOMUNITAS BUDAYA ASEAN - Harini, Setyasih (Transformasi, 2016)
The regional integration process in Asia has been generally considered different nature andpractice. Naturally, ten countries in Southeast Asia has been integrated. It because of geographyand practically they also integrated because of culture. It called ASEAN Socio-CultureCommunity. Ten countries in ASEAN Social and Cultural Community could shared andpromoted national culture in order to further developed. Question research: how did effort toincrease teens nationalism in Baluwarti and Christian Vocational High School toward ASEANSocial and Cultural Community? Nationalism and regionalism as theory of this research. Thiswas qualitative research and it used primary and secondary data. Collecting data techniqueused observation, in depth interview, and study documentary. Analysis data technique used datareduction, display data, and verification. Result of this research showed that national culturewich was based on local culture must be educated to teens specially in Baluwarti and ChristianVocational High School. It could increased nationalism and early step toward impact of ASEANSocio-Culture Community.Key words: ASEAN Socio-Culture Community, nationalism, regionalism